Adakah Pengaruh Peningkatan Transaksi Pembayaran Nontunai terhadap Jumlah Uang Beredar selama Pandemi Covid - 19 - Emilda, Emilda; Nurkholis, Kgs M; Putri, Andini Utari (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This research aims to find out whether there are non-cash payments regarding the amount of money circulating in Indonesia during the Covid-19 pandemic. The money supply used in this research is narrow money (M1) and broad money (M2). Non-cash payments in this research are represented by four transaction schemes, namely the card payment system (APMK), electronic money, Bank Indonesia's national clearing system (SKNBI), and the BI-RTGS system. The Error Correction Model is used to study the relationship between non-cash payment systems and the money supply. Data processing in this research uses Eviews 9. The partial research results show that only the value of electronic transactions has a positive effect on the narrow money supply (M1) and none of the variables from the non-cash payment scheme in this study have a partial effect on the broad money supply (M2). Meanwhile, it simultaneously shows that the value of ATM/Debit transactions, the value of electronic money transactions, the value of credit card transactions, the value of clearing transactions, and the value of BI-RTGS transactions together influence the M1 and M2 money supply.